2007
DOI: 10.1900/rds.2007.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine-Induced Hyperglycemia in Nonobese Diabetic Mice: Kinetics and Mechanisms of Action

Abstract: ■ AbstractThe effects of bromocriptine (10 mg/kg), known to inhibit prolactin secretion and lower autoimmune processes, were studied on glucose homeostasis in non-fasted non-obese diabetic mice, a spontaneous model of type 1 diabetes. Hyperglycemia was observed 120 and 240 min after i.p. but not s.c. injection. Bromocriptine administration i.p. led to rapid and marked hyperglycemia characterized by sexual dimorphism with males having higher glycemia than females. Bromocriptine induced a rapid but transient dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This view is further supported by a recent study that examined BC-induced hyperglycemia and blood corticosterone increases in nonobese diabetic mice [57]. This study also utilized a 10 mg/kg dose of BC and concluded that the BC-induced hyperglycemia and blood corticosterone increases involved D2R since concurrent administration of 10 mg/kg of the D2R antagonist metoclopramide blocked these effects [57]. Another recent study also selectively utilized a 10 mg/kg dosing regimen in combination with Hypericum perforatum (a natural antioxidant) to show reduced 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine (MPTP)-induced neurotoxicity in mice [58].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This view is further supported by a recent study that examined BC-induced hyperglycemia and blood corticosterone increases in nonobese diabetic mice [57]. This study also utilized a 10 mg/kg dose of BC and concluded that the BC-induced hyperglycemia and blood corticosterone increases involved D2R since concurrent administration of 10 mg/kg of the D2R antagonist metoclopramide blocked these effects [57]. Another recent study also selectively utilized a 10 mg/kg dosing regimen in combination with Hypericum perforatum (a natural antioxidant) to show reduced 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine (MPTP)-induced neurotoxicity in mice [58].…”
Section: Discussionmentioning
confidence: 58%
“…Although we cannot directly argue for the results that we report as being D2R and DAT dependent, the fact that we do report changes in D2R and DAT binding which coincide with a reduction in obesity and NAFLD markers using this specific dose and treatment regimen is suggestive of the potential involvement of D2R and DAT in these effects. This view is further supported by a recent study that examined BC-induced hyperglycemia and blood corticosterone increases in nonobese diabetic mice [57]. This study also utilized a 10 mg/kg dose of BC and concluded that the BC-induced hyperglycemia and blood corticosterone increases involved D2R since concurrent administration of 10 mg/kg of the D2R antagonist metoclopramide blocked these effects [57].…”
Section: Discussionmentioning
confidence: 65%
“…In humans, reports of changes in peripheral glucose and insulin concentrations after administration of D2R agonists (Scranton et al, 2007) and antagonists (Pezzarossa et al, 1986) further supports this view. In particular, the D2R agonist bromocriptine currently holds promise as an effective diabetes medication (Durant et al, 2007; Scranton et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…To address this question, we treated mice with bromocriptine, an inhibitor of prolactin production (25,26). The higher level of insulin in transplants of female compared with male recipients at 3 weeks was confirmed again in control mice receiving the placebo.…”
Section: Resultsmentioning
confidence: 99%